Modern Diagnosis of Acquired Heart Defects - Xudoyberdiyev Davlat Gʻayrat oʻgʻli Botirov Sanjar Shuxrat oʻgʻli Narziqulov Shaxboz Baxodir oʻgʻli Raxmonqulov Doniyorbek Davron oʻgʻli (Journal of Science in Medicine and Life, 2024)
The information in this section cannot be used for self-diagnosis and self-treatment. In case of pain or other exacerbation of the disease, diagnostic tests should be prescribed only by the attending physician. You should contact your doctor for a diagnosis and to prescribe the right treatment. Acquired heart defects are a group of diseases in which the normal structure of the heart valves is disturbed, which subsequently leads to problems with blood circulation. The main role in the development of acquired heart defects is played by the body's immunity against group A β-hemolytic streptococcal infection.